Community Dimensions of Smuggling: The Case of Afghanistan and Somalia. Issue 1 (March 2018) - Majidi, Nassim
This article uses an ecological systems approach to detail community involvement in smuggling in Afghanistan and Somalia—two countries that have similar patterns of irregular outmigration to the West and geopolitical and human security dynamics. I emphasize community connections and family ties as the key points around which irregular migration takes place and smuggling persists. In both of these countries, smugglers are members of local communities. The social organization of smuggling is strongest at community-based points of origin, then weakens as migrants and smugglers get farther from their homes, owing to a growing diversity of actors, cultures, and languages. By analyzing the strength of ties in communities involved in smuggling, the dynamics of referrals and guarantees, and interactions across various distances, this analysis takes the focus away from the causal and economic logic of smuggling to delve instead into its relational dimensions.